(3GdYdGbGJ GdYGeI (B:s (3Hjf GdfXQjI h GdJWHjb (B/s - (3YLhI, Ydjs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 2001)
(3jJVef gPG GdcJGH YOOG ef GdOQGSGJ GdJWHjbjI aj GdYdGbGJ GdYGeI h jGJj aj ebOeI gPg GdJWHjbGJ GdYdGbGJ GdYGeI aj GdHfhc h TQcGJ GdJGejfs
Keywords: (3GdHfhcs; (3GdJYdje GdYGdj h GdHMK GdYdejs; (3GdYdGbGJ GdYGeIs